Síntese de campos sonoros através dos modos de radiação ativos e reativos de arranjos planares de fontes acústicas - Clinton André Merlo (2018)
This work investigates how the active and reactive radiation modes of planar loudspeaker arrays can be used in the synthesis of sound fields generated by plane waves impinging on a rigid flat panel, as well as in the synthesis of the random pressure fields generated by diffuse and turbulent boundary layer (TBL) models. Any sound field generated by a source array can be decomposed into its radiation modes, which are related to its radiation efficiencies. Classically, acoustic radiation modes are defined for free far-field condition, so only the active portion of the sound power is considered. However, when the synthesis of the pressure field occurs in the near-field, the reactive portion of the sound power must be considered, which has been little explored in the literature. In this way, the originality of this work consists of the use of the reactive radiation modes in the problems of near-field sound synthesis. The acoustic transfer and particle velocity matrices of the acoustic model, which lead to the matrix that couples the sound power, are determined by numerical simulations involving the finite element method. The active and reactive radiation modes are, respectively, the eigenvectors of the real and imaginary part of the matrix that couples the sound power of the acoustic model. The modal matrix is incorporated into the synthesis method to enable regularization through the most efficient active and reactive radiation modes. By analyzing the control metrics, for several numerical simulations with and without regularization, it is possible to verify the viability of the acoustic model in reproducing random pressure fields whose spatial statistical properties are similar to those of the diffuse and TBL fields